Nonprofits as socially responsible actors: Neoliberalism, institutional structures, and empowerment in the United Nations Global Compact. (May 2022) - Lim, Alwyn
Nonprofit and nongovernmental organizations have become prominent participants in a global organizational responsibility movement. This trend of nonprofit responsibility is puzzling because nonprofits are presumably already dedicated to the pursuit of collective well-being objectives. This article examines the nonprofit responsibility movement from a cultural perspective, whereby broader cultural changes at the level of international organizations have constructed nonprofit entities as empowered and socially responsible actors. Using the case of the United Nations Global Compact, a global framework for corporate social responsibility, the author shows how (1) the construction of cultural meanings of autonomy and decentralization in the neoliberal context, (2) existing institutional structures, and (3) the delegation of responsibility to nonprofit organizations have enabled nonprofit organizations to become active participants in the global organizational responsibility movement. This article utilizes documentary data from the United Nations as well as previously-existing interviews with United Nations officials.